Environmental exposure to mixtures of per- and polyfluoroalkyl substances in Northeast China: exploring links to nodular goiter and papillary thyroid carcinoma - Ziqing Sun; Boying Liu; Rui Ding; Xin Wang; Yanyan Chen; Yi Wang (Environmental Health)
Abstract Background Environmental exposure to per- and polyfluoroalkyl substances (PFAS) has been related to some adverse health effects. An increasing number of people are suffering from nodular goiter (NG) and papillary thyroid carcinoma (PTC), the specific types of thyroid tumors with the highest prevalence. In vivo and in vitro studies have indicated that exposure to PFAS can disrupt thyroid homeostasis and exhibit apparent endocrine-disrupting toxicity, including the decreased thyroid hormone levels and abnormal expression of thyroid-related genes. However, epidemiological evidence supporting the cause-effect relationship between PFAS exposure and the risk of NG and PTC is still lacking. Methods We enrolled 290 participants to explore the relationship between PFAS exposure and NG/PTC risk. 21 urinary PFAS were detected by ultra-high performance liquid chromatography-triple quadrupole mass spectrometry (UPLC-MS/MS). Logistic regression, restricted cubic spline (RCS), Bayesian Kernel Machine Regression (BKMR) and quantile g-computation (qgcomp) models were adopted to examine effects of single and mixed PFAS exposure on NG/PTC risk. Results Our data showed that perfluoroheptane sulfonate (PFHpS) (P = 0.033) and perfluorohexane sulfonate (PFHxS) (P = 0.003) levels in NG cases and perfluoroheptanoic acid (PFHpA) (P = 0.008) levels in PTC cases were significantly higher than those in the controls. After adjustment for confounders, PFHxS was significantly related to higher NG/PTC risk (all P for trend < 0.05). A remarkable non-linear association was found between PFHpA exposure and PTC risk (P-overall < 0.001, P-non-linear = 0.001). The BKMR model indicated that PFAS mixtures significantly increased NG risk, with PFHxS contributing the most (groupPIP: 0.886, condPIP: 0.658). In stratified analyses, PFAS mixtures were positively associated with NG/PTC risk in females and normal-weight subjects. Conclusion Our results suggest that environmental exposure to PFAS mixtures may be associated with increased NG/PTC risk, and each PFAS may contribute to NG/PTC risk in very different ways. To the best of our knowledge, this is the first epidemiological study to examine effects of PFAS exposure on NG/PTC risk.